Ignoring Ecosystem-Service Cascades Undermines Policy for Multifunctional Agricultural Landscapes - Nilsson, Lovisa; Andersson, Georg K. S.; Birkhofer, Klaus; Smith, Henrik G. (Frontiers in Ecology and Evolution, 2017)
Over and above food, agricultural landscapes provide citizens with crucial public-good ecosystem services, such as biodiversity conservation, cultural values, recreational opportunities and food security. Because continuing agricultural intensification undermines the ability of landscapes to provide public goods, policies have been implemented to preserve landscape multifunctionality, but with limited success. We suggest that one reason for this lack of success is that the cascading nature of ecosystem services has not been sufficiently addressed. While different definitions of multifunctionality emphasize different parts of the service cascades, we argue that efficient policies targeting multifunctionality simultaneously need to consider ecosystem services along the entire cascade, i.e. both intermediate and final ones. By understanding how multiple final ecosystem services are promoted by single measures with effects on multiple intermediate ecosystem services or by single intermediate ecosystem services with effects on multiple final ecosystem services, measures can be identified that simultaneously benefit private and public goods, allowing the latter to hitchhike on management for the former. Even if such synergistic solutions are less efficient in terms of promoting yields compared to non-synergistic solutions, policies such as payment for ecosystem services to promote them may be cost-efficient since the private benefit reduces the need for public payment. Furthermore, by focusing on the ecosystem service cascade, social-ecological scale-mismatches along the cascade hampering the implementation of synergistic solutions can be identified and targeted by policy. We exemplify our reasoning with the potential benefit to biodiversity conservation from yield-enhancing ecosystem services.